Effects of extracellular polymeric substances on the aggregation of Aphanizomenon flos-aquae under increasing temperature - Deng, Dailan; Meng, Han; Ma, You; Guo, Yongqi; Wang, Zixuan; He, Huan; Liu, Jin-e; Zhang, Limin (Frontiers in Microbiology, 2022)
Aphanizomenon flos-aquae (A. flos-aquae) blooms are serious environmental and ecological problems. Extracellular polymeric substances (EPSs) are among the most important indicators for the growth and aggregation of A. flos-aquae. In this study, the secretion of the EPS matrix under temperature rise (7°C–37°C) was investigated and the role of this matrix in A. flos-aquae aggregation was quantified. First, when the temperature increased, the aggregation ratio increased from 41.85% to 91.04%. Meanwhile, we found that when soluble EPSs (S-EPSs), loosely bound EPSs (LB-EPSs) and tightly bound EPSs (TB-EPSs) were removed successively, the aggregation ratio decreased from 69.29% to 67.45%, 61.47%, and 41.14%, respectively. Second, the content of polysaccharides in the EPS matrix was higher than the content of proteins under temperature change. The polysaccharide in TB-EPSs was closely related to the aggregation ability of A. flos-aquae (P < 0.01). Third, PARAFAC analysis detected two humic-like substances and one protein-like substance in EPSs. Furthermore, Fourier transforms infrared spectroscopy (FTIR) showed that with increasing temperature, the polysaccharide-related functional groups increased, and the absolute value of the zeta potential decreased. In conclusion, these results indicated that a large number of polysaccharides in TB-EPSs were secreted under increasing temperature, and the polysaccharide-related functional groups increased correspondingly, which reduced the electrostatic repulsion between algal cells, leading to the destruction of the stability of the dispersion system, and then the occurrence of aggregation. This helps us to understand the process of filamentous cyanobacterial aggregation in lakes.